Re-evaluating the gender gap: a cross-sectional analysis of accepted American Academy of Neurology annual meeting abstracts in 2020 and 2021 - Kim, Minseon; Kim, Youngran; Sharrief, Anjail Z.; Nguyen, Thy P. (Frontiers in Research Metrics and Analytics, 2024)
Background and Objective: Prior studies reveal invited speaker panels, editorial boards, senior authors of publications and practice guidelines are disproportionately male in neurology. We aimed to analyze a gender gap in authorship of accepted abstracts to the American Academy of Neurology annual meetings in 2020 and 2021. Design/Methods: This is a cross-sectional study evaluating proportions of female first and senior abstract authors in 2020 and 2021. Abstracts were reviewed manually (n=3211 in 2020; n=2178 in 2021). Data were collected regarding gender of first and senior authors, subspecialty, and origin of research (USA, international, or corporate-affiliated). Then, we compared the percentages of female first and senior authors in the two years, to assess for any short term effects of the pandemic. Results: Accepted abstracts with female first and senior authors respectively comprised 46%, 34% in 2020 and the same in 2021. Female senior authors had a significantly higher proportion of female first authors than male senior author counterparts. The analysis of subspecialties with more than 100 abstracts showed the lowest percentages of female senior authors were oncology (24.7%), sleep (25.5%), headache (28.7%) and cerebrovascular disease (29%) in 2020. Cerebrovascular disease (29%) and behavioral neurology (24.7%) had the lowest percentage of female senior authors in 2021. In analysis of the origin of research, corporate-affiliated had the lowest percentages of female first (34%, 36%) and senior authors (22.6%, 27.6%). Conclusions: The gender gap in neurology was reaffirmed in female senior authorship and abstracts for cerebrovascular, headache, behavioral neurology, sleep, oncology and corporate-affiliated research.